The Effectiveness of Article 31 of Law Number 2 of 2011 Concerning Political Parties - Muzizat, Luluk Kamim; Muhibbin, Moh. (International Journal of Social Service and Research, 2024)
Political parties are national organizations and are one of the important elements in a democratic country. Political parties as political institutions are responsible for providing political education to cadres as well as the general public. Political parties are one of the tools to be able to occupy public positions ranging from the executive to the legislature. Political education is one way or effort to realize a good and quality democratic country. This study aims to discuss and find out how the implementation or implementation of political education in Tuban Regency. The method used in this legal research is the Normative juridical method, Data in this study was obtained from the results of interviews and literature studies for analysis materials. The data analysis technique used is qualitative discriptive. The results showed that the implementation of political education in Tuban Regency has not been maximized both for cadres and for the wider community. Political education is carried out only ahead of the big agenda, namely before the elections both Pilkada, Pileg and Presidential Elections. Political education materials presented by political parties are still not so optimal or less applicable. This has an impact on the number of votes, changes in votes compared to the results of votes in the 2014 election. In addition, it also has an impact on the quality of Party cadres in carrying out party functions and objectives, and affects the level of political participation of the community in granting political rights.